2016
DOI: 10.1021/acs.jpcb.5b07179
|View full text |Cite
|
Sign up to set email alerts
|

High Nucleobase-Solubilizing Ability of Low-Viscous Ionic Liquid/Water Mixtures: Measurements and Mechanism

Abstract: Research on nucleobases has always been on the forefront owing to their ever-increasing demand in the pharmaceutical, agricultural, and other industries. The applications, however, became limited due to their poor solubility in water. Recently, ionic liquids (ILs) have emerged as promising solvents for nucleobase dissolution, as they exhibit >100-fold increased solubility compared to water. But the high viscosity of ILs remains as a bottleneck in the field. Here, by solubility and viscosity measurements, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…The cosolvents are added to overcome this problem; on adding moderate amount of water to ionic liquids, solubility of nucleobases is not affected but the viscosities of the resultant mixtures decrease significantly. 11 In many applications, the cosolvents alter the intermolecular interactions that affect the solubility of sparingly soluble compounds. The solvation nature of the solvent toward a particular solute can be understood by assessing a thermodynamic quantity, solvation free energy.…”
Section: Introductionmentioning
confidence: 99%
“…The cosolvents are added to overcome this problem; on adding moderate amount of water to ionic liquids, solubility of nucleobases is not affected but the viscosities of the resultant mixtures decrease significantly. 11 In many applications, the cosolvents alter the intermolecular interactions that affect the solubility of sparingly soluble compounds. The solvation nature of the solvent toward a particular solute can be understood by assessing a thermodynamic quantity, solvation free energy.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the one-electron redox potentials of the nucleobases by experimental measurements is a very difficult task due to the irreversibility of the process and the low solubility of some nucleobases in water. [1][2][3][4][5][6] In the same way, the computation of the potentials is also challenging due to the several factors that can be considered in the theoretical model by means of different approaches, such as vibrational sampling, solvent effects and the level of theory at which the electronic structure of the nucleobases are described. However, an accurate characterization of the redox properties of nucleobases is crucial to understand the molecular mechanism of different charge-transfer processes in which the DNA constituents are involved, as those occurring in biosensor devices.…”
Section: Introductionmentioning
confidence: 99%
“…While intermolecular electrostatic interaction is the major driving force for the formation of aprotic ILs, protic ILs possess electrostatic interaction vis-à-vis wide varieties of traditional and nontraditional H-bonds. , It has recently been shown that the strong three-dimensional H-bonding network of protic ILs resembles the hydrogen-bonded network of bulk water . Moreover, this class of ILs not only exhibits strong H-bonding in itself but also can induce suitable H-bonding in other molecules …”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, this class of ILs not only exhibits strong H-bonding in itself but also can induce suitable H-bonding in other molecules. 13 Ludwig and co-workers reported H-bond mediated solvation of ILs in water, where the polar water disrupted the strong ionpairing of neat ILs to solvate. 14 Of late, our group and others have confirmed the existence of strong H-bonding interaction in IL/water binary mixtures by MD simulations and other techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation